Radon on Mt. Etna (Italy): a useful tracer of geodynamic processes and a potential health hazard to populations - Giammanco, Salvatore; Bonfanti, Pietro; Neri, Marco (Frontiers in Earth Science, 2023)
Radon gas and its radioactive daughters have been extensively studied on Mt. Etna, both in local volcanic rocks and in all types of fluid emissions from the volcano (crater gases, fumaroles, mofettes, soil gases, groundwaters). The first measurements date back to 1976 and were carried out both in local volcanic rocks and in the crater plume. Since then, fifty-four scientific articles have been published. The largest majority of them (more than 50%) correlated radon emissions with volcanic activity and/or magma dynamics inside Mt. Etna. Many others were focused on possible correlations between time variations of in-soil radon and tectonic activity. The concentration of radionuclides in Etna volcanic rocks was measured in several occasions in order to set background values of radon parents and to study the dynamics of Etna magmas. Some articles analyzed the concentrations of radon in Etna groundwaters and their temporal changes in relation to volcanic activity. Only a few studies focused on methodological aspects of radon measurements in the laboratory. Finally, in recent years, geoscientists began to analyze the possible negative effects on human health from high concentrations of indoor radon in houses near active faults. The overall results show that, in most cases, it is possible to understand the endogenous mechanisms that cause changes in soil radon release from rocks and its migration to the surface. Several physical models were produced to explain how those changes were correlated with Etna’s volcanic activity, making them potential precursors, especially in the cases of eruptive paroxysms. More complex is the analysis of radon changes in relation to tectonic activity. Indeed, if measurements of radon in soil is now considered a robust methodology for identifying buried faults, radon time variations are not always clearly correlated with seismic activity. This difficulty is likely due to the complex interplay between tectonic stress, magma migration/eruption and gas release through faults. In any case, the potential high hazard for human health due to high concentrations of indoor radon in houses close to faults seems to be a well-established fact, which requires particular attention both from the scientific community and the public health authorities.